1997
DOI: 10.1021/bi9622229
|View full text |Cite
|
Sign up to set email alerts
|

A Pulsed-Field Gradient NMR Study of Bovine Pancreatic Trypsin Inhibitor Self-Association

Abstract: Previous studies have produced conflicting interpretations regarding the aggregation state of BPTI in solution. Here, pulsed-field gradient NMR self-association measurements have been performed with BPTI under a variety of temperature, pH, salt, urea conditions, and protein concentrations. Relative to the standard proteins, lysozyme, ribonuclease, and ubiquitin, diffusion constants indicate that BPTI dimerizes at concentrations above about 3 mg/mL and below 280 K. At higher temperatures, a marked self-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 18 publications
4
61
0
Order By: Relevance
“…For example, when the concentration of PDE␥ was lowered from 350 to 90 M, the Ds of PDE␥ increased from 0.92 ϫ 10 Ϫ6 cm 2 ⅐s Ϫ1 to 1.19 ϫ 10 Ϫ6 cm 2 ⅐s Ϫ1 . The measured Ds did not change when the concentration of PDE␥ was lowered from 90 to 45 M. These results suggest that PDE␥ exists as an oligomer at higher concentrations but is monomeric at Ͻ90 M. Furthermore, comparison of the diffusion coefficient for monomeric PDE␥ (10 kDa, Ds ϭ 1.2 ϫ 10 Ϫ6 cm 2 ⅐s Ϫ1 ) with that for monomeric lysozyme (14 kDa, Ds ϭ 1.11 ϫ 10 Ϫ6 cm 2 ⅐s Ϫ1 ) (21), suggested that the structure of PDE␥ in solution is relatively compact, despite its dynamic state.…”
mentioning
confidence: 80%
“…For example, when the concentration of PDE␥ was lowered from 350 to 90 M, the Ds of PDE␥ increased from 0.92 ϫ 10 Ϫ6 cm 2 ⅐s Ϫ1 to 1.19 ϫ 10 Ϫ6 cm 2 ⅐s Ϫ1 . The measured Ds did not change when the concentration of PDE␥ was lowered from 90 to 45 M. These results suggest that PDE␥ exists as an oligomer at higher concentrations but is monomeric at Ͻ90 M. Furthermore, comparison of the diffusion coefficient for monomeric PDE␥ (10 kDa, Ds ϭ 1.2 ϫ 10 Ϫ6 cm 2 ⅐s Ϫ1 ) with that for monomeric lysozyme (14 kDa, Ds ϭ 1.11 ϫ 10 Ϫ6 cm 2 ⅐s Ϫ1 ) (21), suggested that the structure of PDE␥ in solution is relatively compact, despite its dynamic state.…”
mentioning
confidence: 80%
“…The linear plots with similar slopes reflect that the oligomerization states of the monomer and the oligomer do not change significantly over the temperature range studied. 30 The ratio of the diffusion coefficients of the oligomer and the monomer (D oligomer /D monomer ) helps establish the oligomerization state. 28a,32 If both the monomer, and the oligomer are envisioned as compact (spherical) structures, then D oligomer /D monomer should be 0.63 for a tetramer and 0.79 for a dimer.…”
Section: Design Synthesis and Study Of Macrocyclic Peptide 3amentioning
confidence: 99%
“…Translational diffusion measurements were performed on a Varian Inova 500 NMR spectrometer by using the pulse field gradient (PFG) method as described previously (29). Similar PFG-NMR studies have been done to assess the self-association and complexation of other protein systems (e.g.…”
mentioning
confidence: 99%